1993
DOI: 10.1055/s-2008-1063517
|View full text |Cite
|
Sign up to set email alerts
|

DMSA Scintigraphy in Renal Duplex System

Abstract: During a 4-year period 40 children (13 boys and 27 girls) with renal duplex system were examined with DMSA scintigraphy. The age at the investigation varied from 18 days to 9 years, mean 2.5 years. Duplicated system existed in 52 kidneys, bilaterally in 12 cases, right-sided in 10 and left-sided in 18 cases. The renal DMSA scintigraphy of the 52 duplicated kidneys revealed insignificant parenchymal damage in 19 kidneys. Moderate parenchymal damage existed in 10 kidneys. In the remaining 23 kidneys, severely de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…A study by Kullendorff and Wallin, where dimercaptosuccinic acid scintigraphy was used to characterise renal function in identified cases of duplex kidneys found 44% of cases had severely deteriorated function. 18 Our study supports current literature where duplex kidney are found to be up to two times more common in female patients and bilateral in less than 20%. 1,3,8,19 There is the suggestion that inheritance of duplex kidneys may be of a dominant nature with variable penetrance 8,20 ; however, the well-described female predomience is not explained by this.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A study by Kullendorff and Wallin, where dimercaptosuccinic acid scintigraphy was used to characterise renal function in identified cases of duplex kidneys found 44% of cases had severely deteriorated function. 18 Our study supports current literature where duplex kidney are found to be up to two times more common in female patients and bilateral in less than 20%. 1,3,8,19 There is the suggestion that inheritance of duplex kidneys may be of a dominant nature with variable penetrance 8,20 ; however, the well-described female predomience is not explained by this.…”
Section: Discussionsupporting
confidence: 92%
“…This high incidence of complication is similar to the literature. A study by Kullendorff and Wallin, where dimercaptosuccinic acid scintigraphy was used to characterise renal function in identified cases of duplex kidneys found 44% of cases had severely deteriorated function …”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kullendorff and Wallin, where dimercaptosuccinic acid scintigraphy was used to characterise renal function, 44% cases with duplex kidneys had severely deteriorated renal function. 21 Elhadi et al presented a case report of left side duplex kidney with lower moiety renal calculus. 22 Several other studies has also mentioned calculus in urinary tract associated with duplex kidney.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in keeping with those reported previously. In a study of 52 duplicated kidneys, 23 of which showed severely deteriorated function (15 upper‐moiety and nine lower‐pole) Kullendorf and Wallin [ 8] noted the differential function of the affected moiety to be ≤14% (mean 5.7%). They therefore recommended ablative surgery when the affected kidney moiety comprised <14% of the total renal function.…”
Section: Discussionmentioning
confidence: 99%